Farmakologické ovlivnění portální hypertenze a vztah ke genetickému polymorfismu eNOS, oxidačnímu stresu a vazoaktivním tkáňovým působkům - Brůha, Radan (Iga MZ ČR, 2006)
Development of portal hypertension complication can be prevented by pharmacotherapy. Study asses the influence of carvedilol on HVPG and complications development - variceal bleeding, ascites, SBP, hepatopulmonary syndrome. The significance of eNOS polymorphism in portal hypertension is not determined. The aim of study is to establish the correlation between this polymorphism and degree of portal hypertension and presence of complications. Predictive factors of response to portal hypertension therapy are not known. Study evaluates the correlation between treatment response and presence of eNOS polymorphism, concentration of endothelin 1, TNFalfa, Il-2, Il-6, F2 isoprostane, NO production. Study evaluates nonabsorbable disaccharides and antibiotics applied for HE control for their possible impact on the HVPG value and cytokines concentration.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: Oxidative Stress; genetika, lékařská genetika; polymorfismus genetický; Endothelial Cells; Hemorrhage; jaterní cirhóza; oxidační stres; Hypertension, Portal; farmacie a farmakologie; ezofageální a žaludeční varixy; Esophageal and Gastric Varices; Polymorphism, Genetic; Antihypertensive Agents; antihypertenziva; portální hypertenze; angiologie; Liver Cirrhosis; endoteliální buňky; krvácení; hepatologie